A novel preoperative plasma indicator to predict prognoses for patients with esophageal squamous cell carcinoma after radical esophagectomy: fibrinogen-to-lymphocyte ratio - Fan, Ningbo; Chen, Dongni; Zheng, Jiabo; Wen, Zhesheng; Lin, Peng (Cancer management and research, 2019)
The inflammatory microenvironment and hemostatic system are involved in several stages of tumor progression. The aim of this study was to assess the prognostic effect of fibrinogen-to-lymphocyte ratio (FLR) in esophageal squamous cell carcinoma (ESCC) patients who underwent radical esophagectomy. We retrospectively reviewed 673 consecutive patients with ESCC who underwent radical esophagectomy from January 2009 to December 2012 at a major cancer hospital in Guangzhou, southern China. The cutoff points were defined by the X-tile software. The prognostic value of FLR for overall survival (OS), disease-free survival (DFS), and first-year mortality after surgery were analyzed using Cox proportional hazard regression model and logistic regression model. Survival was estimated by the Kaplan-Meier estimator and compared using the log-rank test. The optimal cutoff point of FLR was 3.03. Compared with the FLR-low (≤3.03) group, the FLR-high (>3.03) group included older patients (χ =7.267, =0.007), showed higher postoperative overall morbidity (24.7% vs 14.8%, χ =5.414, =0.020) and tended to die within one year (23.5% vs 10.9%, χ =10.871, =0.001). The FLR-high group showed significant lower 5-year OS rates (41.2% vs 53.7%, log-rank=6.827, =0.009) and 5-year DFS rates (35.3% vs 48.0%, log-rank=5.954, =0.015) than the FLR-low group. Multivariate analyses suggested that high FLR was an independent negative predictor of OS (HR: 1.448, 95%CI: 1.073-1.952, =0.015), DFS (HR: 1.445, 95%CI: 1.084-1.925, =0.012) and first-year mortality (HR: 2.123, 95%CI: 1.157-3.898, =0.015). The preoperative FLR level could be used as a simple, noninvasive, inexpensive, and potentially effective indicator to evaluate the prognosis of ESCC patients following radical esophagectomy.